Cerebrotendinous xanthomatosis: A rare neurodegenerative disorder with characteristic imaging findings - Hamza Ghazali Khan, MBBS; Gaurav Raj, MD; Eshita Yadav, MD; Kaustubh Gupta, MD; Dinkar Kulshreshtha, DM; Ratna, MB, MD; Anshumalini Panda, MD; Yogesh Kumar, MBBS (Radiology Case Reports, 2025)
Cerebrotendinous Xanthomatosis (CTX) is a rare, autosomal recessive lipid storage disorder caused by mutations in the CYP27A1 gene, leading to defective bile acid synthesis and systemic accumulation of cholestanol with characteristic findings on imaging. We present a case of a patient with juvenile-onset bilateral cataract, progressive cognitive decline, spastic paraparesis, behavioral abnormalities and seizures. MRI brain revealed symmetrical T2 hyperintensity and T1 hypointensity in the bilateral dentate nuclei, fronto-parietal atrophy, and nonspecific periventricular white matter changes. Ultrasound and MRI of the Achilles tendon demonstrated xanthomas bilaterally. Based on clinical and imaging features, a diagnosis of CTX was considered and later confirmed by genetic testing. This case highlights the role of neuroimaging in the early diagnosis of CTX, enabling timely initiation of chenodeoxycholic acid (CDCA) therapy, which may arrest or reverse disease progression.